Rearticulating Writing Assessment for Teaching and Learning - Huot, Brian (University Press of Colorado, 2002)
Brian Huot's aim for this book is both ambitious and provocative. He wants to reorient composition studies' view of writing assessment. To accomplish this, he not only has to inspire the field to perceive assessment--generally not the most appreciated area of study--as deeply significant to theory and pedagogy, he also has to counter some common misconceptions about the history of assessment in writing. In (Re)Articulating Writing Assessment, Huot advocates a new understanding, a more optimistic and productive one than we have seen in composition for a very long time. Assessment, as Huot points out, defines what is valued by a teacher or a society. What isn't valued isn't assessed; it tends to disappear from the curriculum. The dark side of this truth is what many teachers find troubling about large scale assessments, as standardized tests don't grant attention or merit to all they should. Instead, assessment has been used as an interested social mechanism for reinscribing current power relations and class systems.